Salon management system - Lim, Jeng Jack (2024)
In this modern globalization era, digitalization process is getting more and more common in our daily life. However, it is rare for a salon in Malaysia to implement salon management system in their business. A salon management system provides a lot of features to a salon to ease their daily operation. In addition, salon management system provides a platform for a salon to store and back up the databases of the whole salon. Hence, a salon should implement salon management to improve the efficiency of processes in salon and to manage the salon. To develop a salon management system, a few existing systems such as SalonAppy, MyCuts, DaySmart and Book & S applications have been reviewed in terms of module, functionalities, strengths and weaknesses. To solve most of the problems raised by the existing systems, project objectives have been discussed for the proposed system. Strengths from all the existing systems are adopted into the proposed system to further enhanced the system. Other than that, in the proposed salon management system, the modules provided are login module, appointment and scheduling module, review module, profile module, virtual queue management module, hairstylist and services module as well as virtual hairstyle try on module. Since there are three users which are customers and hairstylist and admin, mobile application is designed for customers and hairstylists while admin will be using web admin panel. The whole project utilized Rapid Application Development (RAD) methodology and used Flutter programming framework to develop a mobile and web salon management system. The main intention of developing the customer and hairstylist interface into mobile application because mobile device is used by almost everyone and is portable. Realtime database in Firebase is implemented for backend support in this project as appointment scheduling and queue management modules are cloud-based modules and need real-time database support. Furthermore, augmented reality (AR) is implemented in customers side where they can try out some of the virtual hairstyles. In the final stage of development, testing is to be performed to test the whole system after the integration of all the modules. After all modules have passed the testing, the salon management mobile application is ready to be commercialized and used by salon with customization.